Penetapan Kadar Siklamat Pada Minuman Es Pada Pedagang Keliling Di Sekolah Dasar Kota Palu Menggunakan Metode Kromatografi Cair Kinerja Tinggi - Fanda Susan Watung; Qabul Dinanta Utama (Jurnal Teknologi dan Mutu Pangan, 2023)
Cold drink was one of beverage that favored by everyone, including children because the taste was sweet and fresh. This condition encouraged traders to add synthetic sweeteners, for example Cyclamate, which has a cheaper price than sugar. The addition of Cyclamate as sweetener was allowed in cold drinks, but it must meet the specified level requirements. This study aims to find out the content of Cyclamate in cold drinks that was sold by peddlers in an elementary school of Palu city, whether it had met the requirements that had been determined by the government. The assay of Cyclamate was analyzed by High Performance Liquid Chromatography (HPLC) method with an ultraviolet (UV) detector at a wavelength of 314 (nm), which had been derivatized to N,N-dichlorocyclohexylamine using sodium hypochlorite (NaCLO) in acidic solution. Samples were obtained from peddlers who was selling at an elementary school of Palu City. The test results showed that the cyclamate content are as following: Sample (1) = 121.27 mg/Kg, Sample (2) = 17.08 mg/Kg, Sample (3) = 105.61 mg/Kg, Sample (4) = 24.78 mg/Kg, Sample (5) = 121.27 mg/Kg . Based on this result, it can be concluded that the cyclamate content in all samples met the specified content requirements.